2023
DOI: 10.3389/fpls.2023.1105521
|View full text |Cite
|
Sign up to set email alerts
|

Jasmonic acid negatively regulates branch growth in pear

Abstract: The quality of seedlings is an important factor for development of the pear industry. A strong seedling with few branches and suitable internodes is ideal material as a rootstock for grafting and breeding. Several branching mutants of pear rootstocks were identified previously. In the present study, ‘QAU-D03’ (Pyrus communis L.) and it’s mutants were used to explore the mechanism that affects branch formation by conducting phenotypic trait assessment, hormone content analysis, and transcriptome analysis. The m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 58 publications
0
3
0
Order By: Relevance
“…The SPL genes are mainly expressed in meristems and are critical to regulating the branching and vegetative growth of alfalfa plants [ 55 ]. Previous studies indicated that overexpression of SPL13 inhibits the growth of axillary buds and reduces the number of lateral branches [ 56 ]. We found in this study that the SPL4 and SPL9 genes were significantly downregulated after the fruit-thinning treatment ( Figure 10 ).…”
Section: Discussionmentioning
confidence: 99%
“…The SPL genes are mainly expressed in meristems and are critical to regulating the branching and vegetative growth of alfalfa plants [ 55 ]. Previous studies indicated that overexpression of SPL13 inhibits the growth of axillary buds and reduces the number of lateral branches [ 56 ]. We found in this study that the SPL4 and SPL9 genes were significantly downregulated after the fruit-thinning treatment ( Figure 10 ).…”
Section: Discussionmentioning
confidence: 99%
“…Most of the genes significantly decrease at the transcriptional level on activation of axillary buds, which implies that TIFY family genes may be involved in the regulation of branch development. It has been reported that JA negatively regulates the branch growth of pear trees and JA downstream regulatory genes play crucial roles in the regulation of branching [62]. Rapeseed is an important oil crop, and the number of branches determines the number of siliques and ultimately determines yield.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, the levels of jasmonates, including jasmonic acid (JA) and jasmonoyl-isoleucine (JA-Ile), tended to gradually decrease throughout the chilling accumulation period (Gao et al, 2021). A recent study found that jasmonic acid is negatively correlated with vegetative growth, specifically branch growth of pear trees, and suggests that genes related to the jasmonic acid pathway play a critical role in branching regulation (Cheng et al, 2023). These studies indicate the importance of JA in response to chilling exposure and the regulation of vegetative growth cessation, as well as the resumption of growth after the dormancy break (Table 2).…”
Section: Phytohormonesmentioning
confidence: 99%